PENGARUH KEBIJAKAN DIVIDEN, LEVERAGE DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Vera Marcelina, - (2019)
The purpose of this study is to examine Influence of Dividend Policy, Leverage and Profitability to Firm Value. The population used in this study is a manufacturer firm listed on the Indonesia Stock Exchange (BEI) in the period 2014-2017. By using purposive sampling method, it is obtained as many as 53 firm as the study sample. The method of analysis used in this study is multiple linier regression. In this research also include the classical assumption that normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. Results of this study indicate that the Dividend Policy has significant positive effect to Firm Value. While Leverage and Profitability are not significant effect to Firm Value.